Mathematical modeling of moisture properties of terry towel products (Texas Journal of Multidisciplinary Studies, 2021)
This article is about mathematical modeling of the dependence of the moisture properties of different textile fabrics on geometric properties. The article builds a mathematical model of various towel products using the spss statistics program to determine the moisture properties of the hair thread and the geometric parameters of its shape in the fabric.